Model Isoterm Adsorpsi Methylene Blue pada Silika Xerogel Termodifikasi EDA/Cu - Nabilla; Edi Nasra; Budhi Oktavia; Riga; M.Iqbal Saputra Gemasih (MASALIQ, 2026)
Methylene blue is a cationic dye that has the potential to contaminate aquatic environments and therefore requires an effective treatment method, one of which is adsorption. This study aimed to analyze the adsorption isotherm characteristics of methylene blue on EDA/Cu-modified silica xerogel and determine the most appropriate isotherm model. The study was conducted experimentally by varying the initial methylene blue concentration from 400 to 1,100 mg/L under optimum adsorption conditions. The adsorption equilibrium data were analyzed using the Langmuir and Freundlich isotherm models through a linear regression approach. The results showed that the Langmuir model exhibited a higher goodness of fit, with an R² value of 0.9967, than the Freundlich model, which obtained an R² value of 0.5763. Analysis using the Langmuir model yielded a maximum adsorption capacity (Qm) of 235.63 mg/g and a Langmuir constant (KL) of 0.201 L/mg, whereas the Freundlich model yielded a Kf constant of 109.3 and an n value of 6.44. These findings indicate that the adsorption of methylene blue on EDA/Cu-modified silica xerogel is better described by the Langmuir isotherm model, indicating the formation of a monolayer on the relatively homogeneous adsorbent surface. This study strengthens the understanding of the equilibrium adsorption mechanism of dyes on modified silica materials and demonstrates the potential of EDA/Cu-modified silica xerogel as an adsorbent for treating dye-containing wastewater.